Current practices in menstrual management in adolescents with cancer: A national survey of pediatric oncology providers. Issue 12 (23rd August 2019) - Close, Allison G.; Jones, Kelley A.; Landowski, Allison; Switzer, Galen E.; Kazmerski, Traci M.; Miller, Elizabeth; Friehling, Erika
Abstract: Background: Adolescents and young adult (AYA) women with cancer are at risk of heavy menstrual bleeding (HMB) due to thrombocytopenia, coagulopathy, and/or disruption of the hypothalamic‐pituitary‐gonadal axis. Currently, little is known about current practices to help prevent and treat HMB in AYA women with cancer. Methods: We surveyed providers from 100 pediatric oncology centers. Face and content validity were assessed prior to distribution. Descriptive statistics, Chi‐squared and Fisher exact tests were used for analysis. Results: Ninety‐four percent of respondents have recommended preventative menstrual suppression. More than half of respondents agreed that patients with the following types of cancers should receive preventative menstrual suppression: sarcomas, acute leukemias, lymphomas, and germ cell tumors. The most preferred form of menstrual suppression was GnRH agonists. Almost 95% of respondents felt that it is important to consider menstrual suppression and that a formal guideline about initiation of menstrual suppression would be helpful. Only 46% felt comfortable personally managing menstrual suppression. Conclusions: The vast majority of pediatric oncologists who responded to this national survey have used preventative menstrual suppression and feel that it is important to consider in many types of AYA cancers. Although pediatric oncologists are most often managing menstrual suppression, they do not feel comfortable doing so and desire guidelines to help with management. Future studies to assess which patients require menstrual suppression and which menstrual suppression is best tolerated and efficacious is needed.